A Systematic Review of Laser Photobiomodulation Dosimetry and Treatment Protocols in the Management of Medications-Related Osteonecrosis of the Jaws: A Rationalised Consensus for Future Randomised Controlled Clinical Trials - Reem Hanna; Ioana Cristina Miron; Snehal Dalvi; Praveen Arany; René Jean Bensadoun; Stefano Benedicenti (MDPI AG, 2024)
Medication-related osteonecrosis of the jaw (MRONJ) is a debilitating adverse effect of bisphosphates, antiresorptive therapy or antiangiogenic agents that can potentially increase oxidative stress, leading to progressive osteonecrosis of the jaws. Despite the large number of published systematic reviews, there is a lack of potential MRONJ treatment protocols utilising photobiomodulation (PBM) as a single or adjunct therapy for preventive or therapeutic oncology or non-oncology cohort. Hence, this systematic review aimed to evaluate PBM laser efficacy and its dosimetry as a monotherapy or combined with the standard treatments for preventive or therapeutic approach in MRONJ management. The objectives of the review were as follows: (1) to establish PBM dosimetry and treatment protocols for preventive, therapeutic or combined approaches in MRONJ management; (2) to highlight and bridge the literature gaps in MRONJ diagnostics and management; and (3) to suggest rationalised consensus recommendations for future randomised controlled trials (RCTs) through the available evidence-based literature. This review was conducted according to the PRISMA guidelines, and the protocol was registered at PROSPERO under the ID CRD42021238175. A multi-database search was performed to identify articles of clinical studies published from their earliest records until 15 December 2023. The data were extracted from the relevant papers and analysed according to the outcomes selected in this review. In total, 12 out of 126 studies met the eligibility criteria. The striking inconsistent conclusions made by the various authors of the included studies were due to the heterogeneity in the methodology, diagnostic criteria and assessment tools, as well as in the reported outcomes, made it impossible to conduct a meta-analysis. PBM as a single or adjunct treatment modality is effective for MRONJ preventive or therapeutic management, but it was inconclusive to establish a standardised and replicable protocol due to the high risk of bias in a majority of the studies, but it was possible to extrapolate the PBM dosimetry of two studies that were close to the WALT recommended parameters. In conclusion, the authors established suggested rationalised consensus recommendations for future well-designed robust RCTs, utilising PBM as a monotherapy or an adjunct in preventive or therapeutic approach of MRONJ in an oncology and non-oncology cohort. This would pave the path for standardised PBM dosimetry and treatment protocols in MRONJ management.